Protection of Victims of Sexual Harassment in Indonesia: A Legal and Victimological Aspect (Universitas Negeri Semarang, 2023)
Sexual harassment is often a problem in social life in Indonesia. The reason is that according to legal records, violence against girls (KTAP) has increased by 2,341 cases, compared to 1,417 the previous year. The increase from the previous year was 65% and the most cases were cases of incest and added to cases of sexual violence (571 cases) while sexual violence against women with disabilities increased by 47% compared to last year and the most victims were intellectual disabilities. Sexual harassment can be in the form of inappropriate behavior or rape. According to WHO in 2006 every day in the world there are women who are harassed, raped or beaten. The Indonesian Criminal Law (KUHP) which regulates this does not have a proper function, because the rules contained in it are incomplete on this issue. Sexual harassment may not cause physical pain and the like, but it can be emotionally harmful. It is very often that sexual harassment cannot be caught because Indonesian laws are imperfect in dealing with this issue. The concept of harassment in Indonesian law has reduced the significance of the harassment experienced by the victim, and therefore cannot bring justice to the victim.